Technology for the Detection of Ablation Defects in Buffer Layers of High-Voltage Cables - Zeqi Huang; Fei Lu; Yafang Tong; Tianru Shi (IEEE Access, 2022)
This article discusses the main structure of HV cables as well as the characteristics of buffer layers and detection of ablation defects. To effectively detect ablation defects in the buffer layer, two approaches, terahertz time-domain measurements and commercial computed tomography (CT), were used in the laboratory to evaluate samples of cable with these defects and compare different preset conditions for detecting defects. The test results showed that the terahertz time domain measurement method was more sensitive than CT to moisture intrusion into the cable, but terahertz wave energy was reflected on the surface of the aluminum sheath of the cable and could not penetrate the sheath, thus, it was difficult to use this method to detect internal defects. The commercial CT method used X-rays to penetrate the aluminum sheath, and it could effectively obtain data for the three-dimensional reconstruction of each layer of material, other than the copper core. The structure of the cable was mapped through three-dimensional reconstruction using VGstudio Max software, and the three-dimensional map and gray value analysis were combined. The results confirmed that defects with different densities in the buffer layer could be detected by commercial CT. Thus, commercial CT detection methods provide an effective solution for identifying hidden defects in cables and have profound practical significance for the development of methods to detect defects when cables are in use.